Efektivitas Program Bantuan Langsung Tunai (BLT) terhadap Kesejahteraan Masyarakat di Kecamatan Daha Utara Kabupaten Hulu Sungai Selatan - Anita Rahmayanti (LPPM Institut Pendidikan Nusantara Global, 2026)
The Effectiveness of Direct Cash Assistance (BLT) on Community Welfare in North Daha District faces several issues, including limited public knowledge about the program, inaccurate targeting of recipients, misuse of funds, and community dependence on BLT. This study uses a qualitative descriptive approach with primary and secondary data collected through observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing, supported by credibility tests such as prolonged observation, increased persistence, and negative case analysis.The results show that the effectiveness of BLT in North Daha District is not yet optimal. This is seen from: (1) low public understanding of BLT, (2) lack of information and socialization from village officials, (3) inaccurate targeting, (4) BLT funds not meeting community needs, (5) delays in disbursement, (6) continuation of the program, (7) partial achievement of program objectives, (8) BLT helping communities affected by Covid-19, but (9) limited socioeconomic changes, and (10) the program having minimal impact since funds only cover basic necessities.Inhibiting factors include lack of socialization, inaccurate targeting, funds not aligned with needs, delayed disbursement, and no significant economic improvement. Efforts to address these issues include increasing program socialization and ensuring proper recipient verification.Recommendations: Village officials should enhance socialization so the community clearly understands the purpose of BLT, and improve accuracy in selecting recipients. The community is advised not to depend on BLT, to use funds wisely according to their needs, and, if possible, to start small businesses to improve economic independence.